2019
DOI: 10.1136/bmjopen-2018-024767
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of patients to use unused medication returned to the pharmacy by another patient: a cross-sectional survey

Abstract: ObjectivesRedispensing by pharmacies of medication unused by another patient could contribute to optimal use of healthcare resources. This study aimed to assess patient willingness to use medication returned by another patient and patient characteristics associated with this willingness.DesignCross-sectional survey.SettingA total of 41 community and 5 outpatient pharmacies in the Netherlands.ParticipantsTotal of 2215 pharmacy visitors.Primary and secondary outcome measuresPatients completed a questionnaire reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 13 publications
(12 reference statements)
5
29
0
Order By: Relevance
“…Previous studies have shown that patients and stakeholders in the pharmaceutical sector generally accept the concept of reusing dispensed medicines as long as certain criteria are met. Bekker et al [17] investigated patients' willingness to use recycled medicines, McRae et al [18] looked at the same issue through the healthcare professionals' perspective, and Bekker et al [16] went further to collect the views from all related stakeholders. A more systematic analysis of human behaviors for reuse of medicines in the UK was reported by Alhamad et al [19], and the three beliefs based on the TPB were studied using a thematic analysis of the associated attitudes after interviewing the local community.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that patients and stakeholders in the pharmaceutical sector generally accept the concept of reusing dispensed medicines as long as certain criteria are met. Bekker et al [17] investigated patients' willingness to use recycled medicines, McRae et al [18] looked at the same issue through the healthcare professionals' perspective, and Bekker et al [16] went further to collect the views from all related stakeholders. A more systematic analysis of human behaviors for reuse of medicines in the UK was reported by Alhamad et al [19], and the three beliefs based on the TPB were studied using a thematic analysis of the associated attitudes after interviewing the local community.…”
Section: Methodsmentioning
confidence: 99%
“…The reuse of medicines is a behavior that can be studied using behavioral sciences [16,17]. Within this perspective, technologies are essential to facilitate attitude change by validating that the medicines returned back to pharmacies have maintained their quality and are safe to use [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous qualitative research [5][6][7][8][9], the major requirements for reusing dispensed medicines can be classified into three categories: quality, safety and others (see Table 1 for details). Applying IoT technologies to pharmaceutical packaging may be a solution to facilitate the concept of medicine reuse [9].…”
Section: Methodsmentioning
confidence: 99%
“…Previous qualitative studies reveal that stakeholders in the pharmaceutical sector generally accept the concept of medicine reuse if certain quality and safety requirements are met [5][6][7]. The activities of returning and reusing prescribed medicines are human behaviours, and Alhamad et al [8] reported similar requirements that could influence stakeholders' beliefs based on the Theory of Planned Behaviour (TPB).…”
Section: Introductionmentioning
confidence: 99%